The Influence Of Microcatchment Design On Rainwater Harvesting Efficiency In Semi-Arid Regions - Sipi, Natalia (CV. SINAR HOWUHOWU, 2025)
Microcatchment rainwater harvesting systems offer a promising solution for improving water availability in semi-arid regions, where rainfall is both scarce and irregular. This study investigates the impact of different microcatchment designs on the efficiency of rainwater harvesting in semi-arid environments. The research focused on comparing various microcatchment configurations, including differences in catchment area size, shape, soil type, and the presence of drainage and diversion features. Data collected during the rainy season revealed that larger and concave-shaped microcatchments were significantly more efficient in capturing rainwater compared to smaller or convex designs. Additionally, soil type played a crucial role in determining the infiltration rates and water retention capacity of the systems. The study also assessed evaporation losses and suggested that evaporation control measures, such as shaded or covered storage, could further improve efficiency. Hydrological modeling predicted that optimized microcatchments could increase water collection by 30-40% compared to traditional systems. The findings emphasize the importance of tailoring microcatchment designs to local environmental and economic conditions to enhance both water conservation and agricultural productivity in semi-arid regions.